Historical Anthropology of Modern India - Dube, Saurabh (History compass, 2007)
The last three decades have seen acute interchanges between history and anthropology in theoretical and empirical studies. Scholarship on South Asia has reflected these patterns, but it has also reworked such tendencies. Here, significant writings of the 1960s and 1970s brought together processes of history and patterns of culture as part of mutual fields of analysis and description. These emphases have been critically developed more recently. Anthropologists and historians have rethought theory and method, in order not only to crucially conjoin but to explore anew the ‘archive’ and the ‘field’. The blending has produced ‘historical anthropology’: writings that approach and explain in new ways elaborations of caste and community, colonialism and empire, nation and nationalism, domination and resistance, law and politics, myth and kingship, environment and ethnicity, and state and modernity - in the past and the present. Work in historical anthropology focuses on practice, process, and power, and often combines perspectives from gender, postcolonial, and subaltern studies.